Overview of Control Programs for Cattle Diseases in Finland - Autio, Tiina; Tuunainen, Erja; Nauholz, Hannele; Pirkkalainen, Hertta; London, Laura; Pelkonen, Sinikka (Frontiers in Veterinary Science, 2021)
Animal disease control has a long tradition in Finland. The country is free of all EU-regulated cattle diseases of categories A and B. Infectious bovine rhinotracheitis, enzootic bovine leucosis, bovine viral diarrhea, bluetongue, bovine genital campylobacteriosis, and trichomoniasis do not currently exist in the country. The prevalence of paratuberculosis, Mycoplasma bovis, salmonella infection, and Q-fever is low. The geographic location, cold climate, low cattle density, and limited animal imports have contributed to the favorable disease situation. Besides screening for selected regulated diseases, the national disease monitoring program includes periodic active monitoring of non-regulated diseases, which allows assessment of the need for new control measures. The detection of diseases through efficient passive surveillance also plays an important part in disease monitoring. The Finnish cattle population totals 850 000 animals kept on 9 300 cattle farms, with 62 000 suckler cows in 2 100 herds and 260 000 dairy cows in 6 300 herds. Animal Health ETT, an association owned by the dairy and meat industry, keeps a centralized cattle health care register. Animal Health ETT supervises cattle imports and trade within the country and runs voluntary control programs (CP) for selected diseases. Active co-operation between authorities, the cattle industry, Animal Health ETT, and herd health experts enables the efficient planning and implementation of CPs. CPs have been implemented for non-EU-regulated diseases such as salmonella, Mycoplasma bovis, ringworm, and Streptococcus agalactiae. The CP for salmonellosis is compulsory and includes all Salmonella serotypes and all cattle types. It has achieved the goal of keeping the salmonella prevalence under 1% of cattle herds. CPs for M. bovis, ringworm, and S. agalactiae are on a voluntary basis and privately funded. The CP for Mycoplasma was designed in collaboration with national experts and has been implemented since 2013. The CP includes observation of clinical signs, nasal swab sampling from calves, and bulk tank milk and clinical mastitis samples for M. bovis. M. bovis-negative herds gradually achieve lower status levels for M. bovis infection. The general challenge facing voluntary CPs is getting farms to join the programs.